Diversification and dynamic capabilities within construction business models and their impact on firm performance - Filtane, Amanda Alicia (Department of Construction Economics and Management, 2025)
This study focuses on the levels of diversity within construction business models and their impact on business performance. This study examines the impact of diversification and dynamic capabilities on firm performance in the South African construction industry. The author's findings indicate a statistically significant relationship between the international diversification of construction business portfolios and both the diversification of the construction sector and the allocation of resources within construction organisations. A significant correlation exists between physical and human resources and the diversification of the construction sector. The findings provide evidence and validation for the theory of dynamic capabilities as influential factors in the value creation of construction organisations. Additionally, the study highlights the significance of both physical and human resources in ensuring the optimal performance of construction organisations. A study strategy known as "mixed methods" was used, which consisted of employing both quantitative and qualitative approaches for data collection and analysis. Survey data were collected as well as case study firms identified through rigorous qualification criteria, where further detailed observations were made and firm performance data spanning over 5 financial years were analysed and findings discussed. In summary, this doctoral thesis contributes significantly to the advancement of our understanding of construction business models and their impact on organisational performance in South Africa. The research findings presented in this study offer significant insights for both academic researchers and industry practitioners in the construction sector, regarding the interrelationships among international diversification, resource allocation, and dynamic capabilities. In addition, the study developed a programmable coded construction business model framework that enables a more comprehensive examination of construction business models and their resulting performance outcomes. Construction companies can thus make informed decisions and develop strategies to navigate a complex and changing business environment.